Expressão da 17β-hidroxiesteroide desidrogenase tipo 2 (17βHSD2) na endometriose: novas perspectivas - Larissa Milani Coutinho (2021)
Background: Endometriosis is an estrogen-dependent disease. A theory of deficient 17βHSD2 expression in lesions, but not in paired eutopic endometrium, leading to high levels of local estradiol has been described as a potential molecular mechanism for the disease progression. Contradictorily, many studies available in the literature have found expression of 17βHSD2 mRNA in ectopic tissue. Objectives: To evaluate whether the epigenetic influence of microRNAs (has-miR-26b-5p e has-miR-124-3p) could impair post-transcriptionally 17βHSD2 protein synthesis in ectopic lesions. Methodology: This is a prospective cross-sectional study. We obtained a collection of 94 tissue samples: 54 endometriosis lesions (EL); 28 eutopic endometrium (EE); 12 endometrium from women without endometriosis (CE). RT-PCR was performed for evaluating has-miR-26b-5p and has-miR-124-3p expression in ectopic and eutopic endometrium. The 17βHSD2 mRNA expression was evaluated by RT-PCR in the three groups. Western Blotting and immunohistochemistry were used to assess 17βHSD2 expression and localization at protein level. Results: There was no difference in either has-miR-26b-5p or has-miR-124-3p expression between EL and EE. The presence of 17βHSD2 mRNA was similar in the 3 groups, both including and excluding the samples obtained from women in use of hormonal therapy. Higher expression of 17βHSD2 mRNA was detected in EL previously exposed to progestins-only, when compared to EL exposed to COC and EL with no prior exposure to hormone therapies (p<0.05). Conclusions: An aberrant expression of has-miR-26b-5p and has-miR-124-3p in endometriotic lesions is probably not associated with disturbed 17βHSD2 expression in endometriosis. Surprisingly, we could not confirm the deficient 17βHSD2 expression in ectopic lesions. The role of 17βHSD2 in endometriosis may be even more complex than assumed so far, and the regulation of its expression in different clinical scenarios should be further investigated.